One-day surgery in pediatric otolaryngology--10 years' experience - Máchalová, Michaela; Šlapák, Ivo (International journal of pediatric otorhinolaryngology, 2008)
OBJECTIVE: Based on long-term results, to evaluate the safety and efficacy of 1-day surgery in pediatric otolaryngology. METHODS: Clinical records in our surgical day care unit during 10 years of its operation were retrospectively evaluated. RESULTS: From 12,331 children treated on day care unit, for 356 children (2.9%) it was necessary to stay in hospital overnight due to complications. CONCLUSIONS: Based on our results, 1-day surgery is safe and effective and has several advantages including patients' satisfaction, a short hospital stay and therefore cost reduction and shorter waiting time for elective surgery.
Keywords: Ambulatory Surgical Procedures; předškolní dítě; dítě; Otorhinolaryngologic Surgical Procedures; Adolescent; lidé; pooperační komplikace; ambulantní chirurgické výkony; délka pobytu; Length of Stay; retrospektivní studie; otorinolaryngologické chirurgické výkony; Postoperative Complications; Czech Republic; Child, Preschool; Česká republika; Child; Retrospective Studies; mladiství; Humans